Early hematopoietic stem cell transplant is associated with favorable outcomes in children with MDS1. Issue 4 (14th November 2012) - Smith, Angela R.; Christiansen, Ellen C.; Wagner, John E.; Cao, Qing; MacMillan, Margaret L.; Stefanski, Heather E.; Trotz, Barbara A.; Burke, Michael J.; Verneris, Michael R.
Abstract Background Although hematopoietic stem cell transplantation (HSCT) is the treatment of choice for childhood myelodysplastic syndrome (MDS), there is no consensus regarding patient or disease characteristics that predict outcomes. Procedure We reviewed 37 consecutive pediatric MDS patients who received myeloablative HSCT between 1990 and 2010 at a single center. Results Twenty had primary MDS and 17 had secondary MDS. Diagnostic cytogenetics included monosomy 7 (n = 21), trisomy 8 (n = 7) or normal/other (n = 8). According to the modified WHO MDS classification, thirty had refractory cytopenia and seven had refractory anemia with excess blasts. IPSS scores were: low risk (n = 1), intermediate‐1 (n = 15), and intermediate‐2 (n = 21). OS and DFS at 10 years in the entire cohort was 53% and 45%. Relapse at 10 years was 26% and 1 year TRM was 25%. In multivariate analysis, factors associated with improved 3 years DFS were not receiving pre‐HSCT chemotherapy (RR = 0.30, 95% CI 0.10–0.88; P = 0.03) and a shorter interval (<140 days) from time of diagnosis to transplant (RR = 0.27, 95% CI 0.09–0.80; P = 0.02). Three years DFS in patients who did not receive pre‐HSCT chemotherapy and those who had a shorter interval to transplant (n = 16) was 80%. Conclusion These results suggest that children with MDS should be referred for allogeneic HSCT soon after diagnosis and that pre‐HSCT chemotherapy does not appear to improve outcomes. Pediatr Blood Cancer 2013; 60: 705–710. © 2012 Wiley Periodicals, Inc.